Icon: Growth Challenges (Global Business Management Review (GBMR), 2022)
Mr. Amir Ghouri, a young entrepreneur of the Sukkur (Pakistan) successfully started the new venture Known as ICON in retailing after crossing several hurdles erected by regulatory authorities. Mr. Amir inherited the business from his forefathers and tried the diversification after the long stuck up of 30 years. Since his graduation in business studies from the USA, he had come up with two successful ventures in retailing and now considered to be the trend setter in retailing business in the vicinity of Sukkur. In his new venture of ICON he is concerned with the challenges of supply chain and getting sales increased. His ventures are perceived to serve up market; while his new venture of ICON has product ranges for the middle and lower middle class also.